Kandungan Protein dan Serat Kasar Pakan Ayam Broiler (Gallus Domesticus) yang Diberi Tepung Daun Murbei (Morus Alba) dengan Level Berbeda - Irmayani, Irmayani; Lestari, Sofya Anda; Novieta, Intan Dwi (Jurnal Peternakan Lokal, 2024)
One of the things that is very important in the growth of broiler chickens is quality feed or appropriate feed that is rich in nutrients. This research aims to determine the protein and crude fiber content of broiler chicken (Gallus domesticus) feed given mulberry leaf flour (Morus alba) with different levels. This research used a Completely Randomized Design (CRD) consisting of 4 treatments P0 (as Control), P1, P2 and P3. Each treatment was repeated 3 times so that there were 12 units, the levels of feed were as follows. P0: Without treatment 0%. P1: Mulberry leaf meal 1% of the total feed. P2: Mulberry leaf flour 3% of the feed amount. P3: Mulberry leaf flour 5% of the feed amount. Based on the results of research that has been carried out, it can be concluded that the addition of mulberry leaf flour (Morus alba) to crude protein in broiler chicken rations has a significant effect, while crude fiber has no significant effect. The best treatment for crude protein and crude fiber content is as follows. The best treatment for crude protein content was treatment P1 (28.2%) with the addition of 1% mulberry leaf flour. The lowest treatment for crude fiber content was in treatment P1 (6.40%) with the addition of 1% mulberry leaf flour.